LoTSS/HETDEX: Optical quasars: I. Low-frequency radio properties of optically selected quasars - Gurkan, G; Hardcastle, M; Best, P; Morabito, L; Prandoni, I; Jarvis, M; Duncan, K (EDP Sciences, 2019)
The radio-loud/radio-quiet (RL/RQ) dichotomy in quasars is still an open question. Although it is thought that accretion onto supermassive black holes in the centre the host galaxies of quasars is responsible for some radio continuum emission, there is still a debate as to whether star formation or active galactic nuclei (AGN) activity dominate the radio continuum luminosity. To date, radio emission in quasars has been investigated almost exclusively using high-frequency observations in which the Doppler boosting might have an important effect on the measured radio luminosity, whereas extended structures, best observed at low radio frequencies, are not affected by the Doppler enhancement. We used a sample of quasars selected by their optical spectra in conjunction with sensitive and high-resolution low-frequency radio data provided by the LOw Frequency ARray (LOFAR) as part of the LOFAR Two-Metre Sky Survey (LoTSS) to investigate their radio properties using the radio loudness parameter (R =L144 MHz/Li band). The examination of the radio continuum emission and RL/RQ dichotomy in quasars exhibits that quasars show a wide continuum of radio properties (i.e. no clear bimodality in the distribution of ℛ). Radio continuum emission at low frequencies in low-luminosity quasars is consistent with being dominated by star formation. We see a significant albeit weak dependency of ℛ on the source nuclear parameters. For the first time, we are able to resolve radio morphologies of a considerable number of quasars. All these crucial results highlight the impact of the deep and high-resolution low-frequency radio surveys that foreshadow the compelling science cases for the Square Kilometre Array (SKA).